LBAS: An effective pricing mechanism towards video migration in cloud-assisted VoD system - Cong, Xin; Shuang, Kai; Su, Sen; Yang, FangChun; Zi, LingLing (Computer networks (Amsterdam, Netherlands : 1999), 2014)
Migrating video instances to cloud to form a cloud-assisted VoD system is an efficient way to solve the problem of increasing costs in the traditional VoD system. In this paper, we focus on further decreasing the costs in this system. We propose a pricing mechanism named LBAS to allocate video instances from VoD provider’s local servers to cloud platforms. First, a pricing algorithm which conforms to the principle of market is presented to determine the price of each video instance. Then, an auction algorithm which is based on low bid and replaceable instances is proposed to determine the allocation and payment of video instances. At last, in order to avoid the collusion among bidders in low-bid auction, the AEM algorithm is improved. The simulation results demonstrate that the proposed mechanism makes the VoD provider decrease 10% of the costs compared with the VMC strategy.